Answer:
[tex]y-2=3(x-1)[/tex]
Step-by-step explanation:
The point-slope form of a line is given as:
[tex]y-y_1=m(x-x_1)[/tex]
Where
m is the slope
[tex]x_1[/tex] is the x-coordinate of the point given (passing through the line)
[tex]y_1[/tex] is the y-coordinate of the point given (passing through the line)
Now,
Given,
Slope = m = 3
[tex]x_1[/tex] = 1
[tex]y_1[/tex] = 2
Now, we simply plug these into the formula for point-slope form of a line:
[tex]y-y_1=m(x-x_1)\\y-2=3(x-1)[/tex]
This is the point-slope form.